Urgensi Pelaksanaan Islamic Corporate Governance (Suatu Kajian Studi Literatur Pada Lembaga Keuangan Syariah) - Siregar, Nurul Inayah (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2023)
Basically, companies and Islamic financial institutions are required to apply the principles of good governance. However, fraud in companies and institutions often occurs and cannot be avoided. In practice, Islamic banks still use the same principles as conventional institutions. This research is a literature study on the implementation of Islamic Corporate Governance in Islamic Financial Institutions, so that it can be seen what discussion has been researched and what discussion needs to be researched. This study uses a qualitative approach. There are 9 articles published in 2018 to 2022 which are grouped into three topics of discussion, namely: 1) Implementation of Islamic Corporate Governance in Islamic Banks, 2) Implementation of Islamic Corporate Governance in Non-Bank Institutions and 3) Implementation of Islamic Corporate Governance associated with Islamic Social Responsibility . Implementation of Islamic Corporate Governance in Islamic Banks is the most articles with a presentation of 44.4%. While the least discussed article is the Implementation of Islamic Corporate Governance associated with Islamic Social Responsibility, with a presentation of 22.2% of the overall theme of the Urgency of Implementing Islamic Corporate Governance in Islamic Financial Institutions. Discussions that need to be examined, such as: Islamic Corporate Governance principles that are in accordance with sharia and different from Corporate Governance principles in general are implemented in conventional institutions